Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, B.M. (South African Journal of Higher Education, 2018)
Using a post structural lens, I make arguments against homogenizing people’s conditions and circumstances. In particular, I acknowledge that the post 1994-reform agenda intended to streamline the previously fragmented and segregated landscape. Black women, who are the main target of this article suffered triple marginalization- race, social class and sexism. The aim of the article is to show the tensions within White Paper (1997)- (A programme for the transformation of higher Education) that have not enabled gender gaps within post 1994 South African higher education addressed successfully- the gaps are still gapping. I state that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group. Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlook on the divergent needs of black women as a possible solution to the current challenges.